Paul versus Baerveldt 350 glaucoma drainage implants: One-year comparative analysis - David Oliver-Gutiérrez; Gloria Segura-Duch; Elena Ávila-Marrón; Carlos A. Arciniegas-Perasso; Susana Duch-Tuesta (Indian Journal of Ophthalmology)
Purpose: This study aimed to evaluate and compare the effectiveness and safety of Paul glaucoma implant (PGI) and Baerveldt 350 glaucoma implant (BGI) over a 1-year follow-up period. Methods: This retrospective study was conducted in a private clinic. It compared 27 patients consecutively treated with the PGI to a historical cohort of 29 eyes that received the BGI prior to the introduction of the PGI between 2018 and 2023. Intervention: A new drainage device, the Paul implant, was placed in the anterior or posterior chamber of eyes with uncontrolled intraocular pressure (IOP). Main Outcome Measures: The main outcome measures were success rate, final mean IOP, IOP reduction percentage, medication reduction, and complications. Statistical analyses, including adjustments for confounders, were used to compare the performance of PGI and BGI over at least a 12-month period. Results: Significant reductions in IOP were observed in both groups (P < 0.001). At 1 year, no significant differences were found in mean IOP (BGI: 12.0 mmHg, SD 2.9; PGI: 11.2 mmHg, SD 6.0) or medication usage (P > 0.05). The failure rates were 7% for BGI and 18% for PGI, with complete success rates of 56% for BGI and 32% for PGI. Hypertensive phases occurred in 32% of the BGI cases and in 19% of the PGI cases. No significant differences in the complication rates or postoperative visual acuity were observed between the groups. Conclusion: PGI and BGI exhibited comparable efficacy and safety profiles after 1 year.